Pirandello’s Spatial Use in the Odescalchi Theatre: The Architectural Representation of Henry IV and Six Characters in Search of an Author - Manuel Iglesias-Vázquez (Buildings)
The interdisciplinary nature of theatre studies often results in research that places greater emphasis on literary analysis than on architectural considerations. Consequently, theatrical literature tends to focus more on the relationship between text, author, and context, rather than on the interaction between the text and the spatiality shaped by the architecture of the performance space of the building. This research introduces and applies a mixed methodology to examine the use of theatrical space in dramatic works, concentrating on the architectural study of paratexts, which shows the influence of literature on the architectural design process of the theater building. This study focuses on the works of Luigi Pirandello, particularly Henry IV and Six Characters in Search of an Author, exploring their influence on the Odescalchi Theatre in Rome, and vice versa. This combined approach, alongside the theatrical qualities of the texts, allows for a detailed analysis of how architecture and spatiality are represented in Pirandellian metaproductions. The findings and their architectural modelling highlight the relationship between literature and theatrical spatiality, providing a quantifiable connection in each of the works examined.